Resetting Humanity for Sustainable Futures of Work & Education in The Asian Century - Samuel Leong (Future Science, 2023)
Humanity has entered one of the most exciting yet most dangerous periods of human history. The seemingly utopian future promised by AI is fraught with megathreats confronting governments and education and business leadership. This paper puts forth the Human Imperative as a non-negotiable for addressing humanity’s diverse challenges in the Asian Century, the epoch of Anthropocene, and the Fourth Industrial Revolution. Following a discussion on a range of key global developments, the paper argues that it is time for a critical Human Reset in the face of global head-winds of disruptions, a global learning crisis, and a global mental health crisis. Human wisdom and virtues encapsulated in the arts, culture, education, languages, and literature should be harnessed to attain sustainable futures for our future generations. (127 words).